Validity and reproducibility of Ki‐67 assessment in gastrointestinal stromal tumors and leiomyosarcomas. (22nd February 2013) - Ogino, Jiro; Asanuma, Hiroko; Hatanaka, Yutaka; Matsuno, Yoshihiro; Gotoda, Hiroko; Muraoka, Shunji; Tsuji, Takayuki; Fukazawa, Yuichiro; Yamashiro, Katsushige; Kondo, Nobuo; Iwaki, Hiroyuki; Miyokawa, Naoyuki; et al.
<x xml:space="preserve">Abstract</x> With the aim of standardizing Ki‐67 immunohistochemistry, we assessed interobserver and interlaboratory variability of the Ki‐67 labeling index and Ki‐67 score among eight general pathologists for 24 gastrointestinal stromal tumors (GISTs) and 12 leiomyosarcomas, which were predominantly of the gastrointestinal (GI) tract, mesentery and retroperitoneum, based on a review of a tissue microarrays subjected to immunohistochemistry with antibodies for Ki‐67. For Ki‐67 immunostaining of mesenchymal tumors of the GI tract, including GISTs, differences were seen in the scores given by regional hospitals. Conversely, for two categories of the Ki‐67 labeling index, namely <10% and ≥10%, concordance of the Ki‐67 score between microscopic observation and image analysis, and between the observers, was good, but it was not good for the other four categories of the index for <5%, 5–9%, 10–29%, and ≥30%. The concordance of the Ki‐67 scores between the observers in two categories was higher using the Ki‐67 pre‐stained tissue microarrays (TMAs) within each participating institute than that using the Ki‐67 stained TMAs between the participating institutes. The reproducibility of a 10% cut‐off value for the Ki‐67 labeling index to predict the prognosis of GISTs was relatively high, but there is an urgent need to standardize the staining technique.